Tentorial meningioma supplied by a marginal tentorial artery arising from the superior cerebellar artery: Anatomic and technical considerations. Issue 4 (August 2017) - Lenck, Stéphanie; Watanabe, Kentaro; Saint-Maurice, Jean-Pierre; Labidi, Moujahed; Labeyrie, Marc-Antoine; Froelich, Sébastien; Houdart, Emmanuel
Background and importance: The marginal tentorial artery runs over the free edge of the tentorium. Different origins have been described, always involving branches of the carotid artery. We report the superior cerebellar artery as an unknown origin of this artery. We developed our strategy in a case of a tentorial meningioma mainly supplied by this artery. Clinical presentation: A 53-year-old man was admitted in our institution for the surgical treatment of a large tentorial and petroclival meningioma. A 2D conventional angiogram was insufficient to detect the tumoral blush. A 3D digital subtraction angiogram (DSA) of the vertebral artery highlighted a blush arising from a marginal tentorial artery fed by the superior cerebellar artery. Selective embolization of this branch led to significant devascularization of the tumor. A total tumor resection was performed 24 h after embolization without complication. The dural medial tentorial artery of the superior cerebellar artery is relatively unknown and courses at the inferior surface of the tentorium. We report the first case in which the marginal tentorial artery arises from this artery. Major bleeding may result from its section or its avulsion from the superior cerebellar artery during surgery; its preoperative diagnosis is thus essential. In this case, a 3D-DSA with dual volume visualization was more sensitive than a 2D conventional angiogram to detect such an anatomic variant. Conclusion: The marginal tentorial artery may originate from the superior cerebellar artery. The recognition of this anatomic variant may be essential to avoid hemorrhagic complications during surgery of hypervascular tumors of the tentorium.